Situated cognition and narrative heuristic: evidence from retail investors and their brokers. Issue 8 (14th July 2016) - Tarim, Emre
Abstract : In this paper, I discuss how a situated cognition perspective can reveal the socially constructed nature of seemingly psychological heuristics and errors in market actors' judgements and decisions in financial markets. In doing so, I present a complementary approach to the heuristics and biases research in psychology and behavioural finance. More specifically, I draw on the narrative mode of knowing and explanation in real market settings as a framework to understand the content and the process of socially constructed knowledge in financial markets. Here, narratives of market actors and their underlying frames and causal schemas are assumed to function as a judgement heuristic in processing information flows. I then discuss an application of this approach to a sample of brokerage firms and investment advisers serving retail investors in the Istanbul Stock Exchange (ISE). My findings focus on a shared frame and the associated causal schema about the ISE and global financial markets. This observed interpretive model underpinned my interlocutors' narrative judgements and forecasts about the ISE's movements and constituted a form of representativeness heuristic and anchoring.